Current concepts on etiology of the pathogenetic mechanisms related to chronic endometritis - D. E. Galkina; T. A. Makarenko (IRBIS LLC, 2023)
Introduction. Due to the rapidly current reproductive technologies developing in recent years, much attention has been paid to patients who suffered from infertility (up to 55 %) mainly caused by chronic endometritis (CE). Due to the lack of prominent and specific clinical manifestations, laborious microscopic examination necessary for diagnostics, CE often receives no proper clinical attention. However, the undeniable relationship between CE and conditions associated with infertility such as repeated unsuccessful implantations and habitual miscarriage, dictates a need to expand knowledge about etiology and pathogenesis of this pathology in order to develop both highly informative diagnostic methods and create effective therapeutic regimens.  Aim: to analyze the literature data on CE pathogenetic mechanisms.  Materials and Methods. The available publications were searched in the databases Web of Science, eLIBRARY, Scopus, PubMed/MEDLINE released within the 1995-2022 period aimed at assessing CE pathogenetic and morphological features using query "chronic endometritis", "plasmocellular endometritis", "endometrial receptivity", "primary infertility", "secondary infertility", "implantation window". To avoid omission of suitable articles, a methodological filter was not applied. There were included full-text sources and literary reviews on the subject under study. Articles directly unrelated to CE topic were excluded from the review. In order to avoid inclusion of duplicate publications in the literature review if two studies by the same authors were found, the study period of each author was examined, and if the dates of publication coincided, most recent publication were used.  Results. New morphological, immunohistochemical, genetic and immunological aspects of СЕ were summarized. The presence of plasma cells is the "gold standard" for CE morphological diagnostics, but their similarity to fibroblasts complicates histological examination and requires using expanded range of diagnostic markers. Thus, in CE patients, were identified a reduced expression of NK cells, with increased level of CD3+, CD+8, CD20+, CD138+ cells as well as pro-inflammatory factors, such as tumor necrosis factor-α - by 3-fold, interleukin-6 - by 2.7-fold, interleukin-8 - by 1.2-fold, interferon-γ - by 1.4-fold compared to healthy women. Special attention is paid to the features of hormone receptor network in chronic endometrial inflammation regarding reproductive losses in infertile women, while a favorable marker for successful pregnancy turned out to be the ratio of progesterone and estrogen receptors ranging from 2 to 3.  Conclusion. Thus, CE rate in the pattern of the causes of infertility and unfavorable reproductive outcomes can up to reach 50 %, however, due to the difficulties of morphological diagnostics, verification of this diagnosis is complicated. The wide range of pathogenetic features of developing chronic inflammation in the endometrium highlighted here may be promising not only for identification of diagnostic markers, but also forimproving endometrialregenerative ability,whichwill increase odds for successfully executed reproductive function in infertile women.